Matüridi’de nesh problemi - Akçay, Murat (My University, 2013)
Bu çalışmada Mâtürîdî’nin ilk devirlerden itibaren sıkça tartışılan nesh konusuna bakışı incelenmiştir. O’na göre nesh, bir vakte kadar geçerli olan hükmün sona erdiğini beyan etmektir. Neshin hikmetini imtihan terimiyle açıklayan Mâtürîdî, neshin bütün çeşitlerini kabul etmiştir. O, nesh meselesine ihtiyatlı bir şekilde yaklaşarak meseleleri olgu ve olaylardan kopuk bir şekilde değerlendirmeyip olgu-lafız ilişkisini gözeterek değerlendirmiştir. Nesh teorisine din-şeriat ayrımını temellendirmek için başvurmuş olup, Kur’ân’la Hz. Muhammed’e gönderilen şeriatın, daha önceki peygamberlerin dinini değil, şeriatlarını neshettiğini ve Hz. Muhammed şeriatının kıyamete kadar geçerli olduğunu vurgulamıştır. O, tarihselcilere göre indirildiği ilk muhatap kitle için bağlayıcı kabul edilip sonraki zamanlarda yaşayanlara doğrudan hitap etmeyen Kur’ân’ın bildirdiği korku namazı, hırsızlığa verilen had cezası ve zıhâr uygulaması gibi hükümleri yerel-mahallî olarak değil de evrensel olarak değerlendirmiştir. Anahtar Kavramlar: Nesh ve çeşitleri, Mâtürîdî, Tarihsellik.

In this study, the view of Maturidi about the subject of nesh which has been frequently discussed as from the early ages has been analyzed. According to him, nesh is to express that a judgment that was valid until a certain time has expired. Maturidi who has explained the philosophy of nesh with the term of examination has accepted all forms of nesh. He has approached the matter of nesh temperately and evaluated the matters by observing the relation of fact and wording, not disjointedly from facts and events. Having referred to the theory of nesh in order to found the distinction of religion-sharia, he has emphasized that the shariah sent to Muhammad with Koran has overruled the sharia of former prophets, not their religions, and that the sharia of Mohammad is valid until doomsday. He has universally, not locally-endemically, evaluated the judgments such as fear salaat, limitation punishment inflicted for robbery and zihar practice which have been stated by Koran and, according to historicists, have been accepted obligatory for the first addressed audience and have not directly appealed to the ones who live in following periods. Key Terms: Nesh and its forms, Maturidi, Historicity.
Keywords: Dini Yaşam; İslam; Kelam; Maturidi, Muhammad ibn Muhammad, d. 944 or 5; Müslüman Alimler